Encapsulation of cinnamaldehyde into nanostructured chitosan films. Issue 13 (10th December 2014) - Rieger, Katrina A.; Eagan, Nathaniel M.; Schiffman, Jessica D.
ABSTRACT Recently, bioactive chitosan films featuring naturally derived essential oils have attracted much attention due to their intrinsic antimicrobial properties and applicability to a broad range of applications. Previously, the ability to form thick (t > 100 µm), chitosan‐essential oil films via solution casting has been demonstrated. However, the fabrication of well characterized ultrathin films (t < 200 nm) that contain essential oils remain unreported. Here, we systematically investigate increasing the incorporation of an essential oil, cinnamaldehyde (CIN) into ultrathin chitosan films. Films with and without the surfactant Span®80 were spin‐coated. Qualitatively, films exhibited well‐defined structural color, which quantitatively ranged from 145 to 345 nm thick. Release studies confirmed that a 6× higher release of CIN was enabled by Span®80 versus the chitosan control films, 30 µg versus 5 µg, respectively. These results suggest that nanostructured chitosan‐CIN coatings hold potential to delay bacterial colonization on a range of surfaces, from indwelling medical device to food processing surfaces. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41739.